1989
DOI: 10.1002/jez.1402490314
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine release by catecholamines in the eel does not require the presence of brain or anterior spinal cord

Abstract: The catecholamine-producing chromaffin cells of the American eel are strongly innervated by fibers, which, by ultrastructural criteria, seem to be cholinergic. However, neither removal of the brain nor removal of the brain combined with extirpation of the anterior spinal cord prevents the release of catecholamines into the circulation by catecholamines. It appears that the chromaffin cells are controlled by both nervous and humoral stimuli, and that at least some of the latter do not require the presence of "p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…Although previous studies have reported catecholaminotropic activity of catecholamines in the eel (Anguilla rostrata; Hathaway et al 1989) and lamprey (Petromyzon marinus; Dashow & Epple 1983), no such interactions were observed in this study. In agreement with former studies conducted in vivo in trout (Perry & Vermette 1987) and in situ in Atlantic cod (Gadus morhua) (Perry et al 1991), the presence of high levels of adrenaline and noradrenaline did not affect the basal secretion of catecholamines from trout chromaffin cells.…”
Section: Effects Of Catecholamines On Catecholamine Releasecontrasting
confidence: 97%
See 1 more Smart Citation
“…Although previous studies have reported catecholaminotropic activity of catecholamines in the eel (Anguilla rostrata; Hathaway et al 1989) and lamprey (Petromyzon marinus; Dashow & Epple 1983), no such interactions were observed in this study. In agreement with former studies conducted in vivo in trout (Perry & Vermette 1987) and in situ in Atlantic cod (Gadus morhua) (Perry et al 1991), the presence of high levels of adrenaline and noradrenaline did not affect the basal secretion of catecholamines from trout chromaffin cells.…”
Section: Effects Of Catecholamines On Catecholamine Releasecontrasting
confidence: 97%
“…In lamprey (Petromyzon marinus) and American eel (Anguilla anguilla), administration of adrenaline or noradrenaline in vivo causes the elevation of plasma catecholamines (both adrenaline and noradrenaline) (Dashow & Epple 1983, Hathaway et al 1989. Furthermore, pre-treatment with -or -adrenergic receptor antagonists decreases catecholamine release in the eel in response to neuronal or cholinergic stimulation of the chromaffin tissue in situ or in vitro (Al-Kharrat et al 1997, Abele et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly the primary mechanism leading to the secretion of catecholamines from the chromaffin cells in teleost and elasmobranch fish is stimulation of these cells by the sympathetic nervous system [2,116,199,201,202,219]. More precisely, chromaffin cells are innervated by pre-ganglionic sympathetic fibers which release the neurotransmitter acetylcholine (Ach) (and possibly others; [112,237,284]) onto the chromaffin cells where it interacts, with cholinergic receptors (cholinoceptors), to initiate the secretion of catecholamines via exocytosis ( [37]; Fig.…”
Section: Chromaffin Cell Cholinoceptor Pharmacologymentioning
confidence: 99%
“…While only adrenaline caused a dose-related increase of plasma dopamine and noradrenaline in the lamprey [65], each of the three catecholamines stimulated the release of the respective other two in A. rostrata [79]. In the eel, these catecholaminotropic effects were unaffected by denervation of the chromaffin tissue in the head kidney [116]. In rainbow trout, continuous infusion of adrenaline does not effect the circulating levels of noradrenaline [218].…”
Section: 228mentioning
confidence: 99%